Impacto da escassez hídrica na agricultura irrigada e estratégia de cultivo e manejo da irrigação em condições de déficit hídrico - Pimentel, Jamili Nobre Fiusa (2021)
Considering that the water scarcity present in the semiarid region causes serious economic and social losses, with the reduction of efficiency and productive capacity, the importance of the continuity of the water regime in fundamental periods for the development of crops is emphasized. Therefore, the research aimed to analyze the impact of water scarcity on the social and economic dimension of public irrigation projects by Dnocs and to determine the response coefficient (Ky) of crops of commercial interest to the Brazilian semiarid region with a view to planning irrigated areas in semiarid regions. Secondary data were obtained from the informative syntheses of public irrigation projects of Dnocs, related to irrigated areas, cultivated areas and Gross Value of Plant Production (VBP) in the periods from 2013 to 2019, in addition to the survey of data to quantify the deficit coefficient (Ky) of crops of interest to the semiarid region. The reduction in the irrigated area and in the gross value of production in the public irrigation projects of Dnocs in the period from 2013 to 2017 was of the same magnitude and around 50%, resulting from the water crisis in the Brazilian semiarid region in this period. In Ceará, the irrigated area decreased 54.2%, however, in the State of Piauí, the irrigated area grew 63.6% in the same period, considering that there is water source from perennial rivers. The Ky results obtained in this research that differ from the results obtained by FAO are associated with climatic differences and/or cultivars used. Cunhã and tanzania grass, due to their low sensitivity to water deficit, show, respectively, high potential to compose a protein bank and as a grass in pasture areas for dairy cattle, an activity that is rapidly expanding in some public irrigation projects in the Brazilian semiarid region. The inclusion of the dwarf cashew tree in the planning of irrigated areas in the semiarid, an environment of low water guarantee, although a perennial crop, becomes a viable alternative, given its high resistance to water deficit.